2021
DOI: 10.7554/elife.65672
|View full text |Cite
|
Sign up to set email alerts
|

Myogenin controls via AKAP6 non-centrosomal microtubule-organizing center formation at the nuclear envelope

Abstract: Non-centrosomal microtubule organizing centers (MTOC) are pivotal for the function of multiple cell types, but the processes initiating their formation are unknown. Here, we find that the transcription factor myogenin is required in murine myoblasts for the localization of MTOC proteins to the nuclear envelope. Moreover, myogenin is sufficient in fibroblasts for nuclear envelope MTOC (NE-MTOC) formation and centrosome attenuation. Bioinformatics combined with loss- and gain-of-function experiments identified i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…It was proven to be a good model for understanding centrosomal and non-centrosomal MT nucleation due to the intensive morphological changes and organelle movement in the post-meiotic spermatids 1517 . MT nucleation was reported, among others, at the surface of the Golgi 40 , mitochondria 16 , nuclear envelope 41 and plasma membrane 42 in mammalian cells. We previously identified and described the function and versatile localization of three testis-specific γ-TuRC proteins in the post-meiotic spermatids 15 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 83%
“…It was proven to be a good model for understanding centrosomal and non-centrosomal MT nucleation due to the intensive morphological changes and organelle movement in the post-meiotic spermatids 1517 . MT nucleation was reported, among others, at the surface of the Golgi 40 , mitochondria 16 , nuclear envelope 41 and plasma membrane 42 in mammalian cells. We previously identified and described the function and versatile localization of three testis-specific γ-TuRC proteins in the post-meiotic spermatids 15 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 83%
“…Formation of a NE-MTOC occurs concomitantly with the differential expression and up-regulation of nesprin-1α2 [ 30 , 33 ], with the N-terminal domain of nesprin-1α2 (equivalent to nesprin-1 giant SR 72 and 73) directly interacting with AKAP6β (referred to as AKAP6), a muscle-specific scaffolding protein [ 34 , 57 ]. Recent studies suggest, upon myogenic differentiation, up-regulation of myogenic regulatory factors (MRFs) promote the expression of nesprin-1α2 and AKAP6 as an initial trigger for NE-MTOC formation, creating a scaffolding platform for the NE targeting of centrosomal proteins AKAP9, pericentriolar material-1 (PCM-1), and pericentrin (PCNT), which form the MTOC at the NE [ 50 , 58 ]. Moreover, a BioID proximity study revealed nesprin-1α2 to be closely associated with AKAP6, AKAP9 (also known as AKAP450), PCM-1, and PCNT in myotubes ( Table 1 ) [ 33 ].…”
Section: Roles Of Nesprin-1/1α2 and The Linc Complex In Striated Musclementioning
confidence: 99%
“…Furthermore, depletion of nesprin-1 resulted in the loss of PCM-1, PCNT and γ-tubulin from myotube nuclei [ 50 ]. Patient derived myoblasts lacking nesprin-1α2 by a SYNE1 nonsense mutation (25360 G > T) exhibit mislocalisation of centrosomal proteins, together indicating a unique role for nesprin-1α2 as the NE-MTOC anchor protein in striated muscle cells [ 58 ].…”
Section: Roles Of Nesprin-1/1α2 and The Linc Complex In Striated Musclementioning
confidence: 99%
“…This involves the reorganization and relocation of the centrosome, Golgi and endoplasmic reticulum exit sites (Bugnard et al, 2005;Zaal et al, 2011). The muscle-specific transcription factors MyoD (also known as MYOD1) and myogenin control the expression of nuclear membrane proteins [nesprin 1α (encoded by SYNE1) and A-kinase anchor protein 6 (AKAP6), respectively], which together with PCM and CS proteins nucleate a non-centrosomal MTOC at the nuclear envelope (Becker et al, 2021;Espigat-Georger et al, 2016;Gimpel et al, 2017;Srsen et al, 2009;Steinfeldt et al, 2021) (Fig. 2).…”
Section: Centrosome Reorganization In Differentiationmentioning
confidence: 99%